Method for passivating back interface of copper-zinc-tin-sulfur-selenium solar cell based on silicon dioxide nanoparticles
By coating the back electrode substrate of copper, zinc, tin, sulfur and selenium solar cells with silica nanoparticles solution to form a back electrode substrate with dispersed silica nanoparticles on the surface, the back interface carrier recombination problem is solved and the battery is improved Open circuit voltage, fill factor and photoelectric conversion efficiency are suitable for large-scale production.
Patent Information
- Application Number
- CN202411547395.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The open circuit voltage (VOC) and fill factor (FF) of existing copper-zinc-tin-sulphur-selenium (CZTSSe) solar cells are limited by back interface carrier recombination, and the commonly used passivation layer materials are complex to diffuse and operate during high-temperature selenization. , it is difficult to achieve efficient battery performance.
By uniformly coating the silica nanoparticle solution with a mass fraction of 0.14% to 1.5% on the back electrode substrate of the copper-zinc-tin-sulfur-selenium solar cell, it is cooled after heat treatment to form a back electrode substrate with surface dispersed silica nanoparticles. Thus, the back interface is passivated and carrier recombination is reduced.
This method improves the open circuit voltage (VOC), fill factor (FF) and photoelectric conversion efficiency of CZTSSe solar cells. At the same time, the process is simple and suitable for large-scale production, and does not diffuse to the absorption layer during high-temperature selenization.
Smart Images

Figure HDA0005114149060000011 
Figure HDA0005114149060000012 
Figure HDA0005114149060000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thin-film solar cells, and more specifically, relates to a method for passivating the back interface of a copper-zinc-tin-sulfur-selenium solar cell based on silicon dioxide nanoparticles. Background Art
[0002] The demand for energy in society is constantly increasing. Compared with traditional fossil energy, solar energy stands out from the sustainable and renewable new energy industry due to its universality, simple accessibility and clean and pollution-free sustainability. Among them, compared with traditional thin-film solar cells, copper zinc tin sulfur selenium (Cu2ZnSn(S,Se)4, CZTSSe) thin-film solar cells have the advantages of adjustable band gap (adjustable between 1.0 and 1.5eV), non-toxicity, high light absorption coefficient, low requirements for raw material purity and low price, so people have been committed to improving the energy conversion efficiency of CZTSSe solar cells.
[0003] The enhancement of conversion efficiency in CZTSSe solar cells is mainly affected by the open circuit voltage (V OC ) and fill factor (FF), which affects V OC The factors of FF are mainly attributed to the obvious carrier recombination at the back interface (Mo / CZTSSe). During the high-temperature selenization process, due to the insufficient thermodynamic stability inside the back interface, secondary phases such as Cu2(S,Se), Zn(S,Se), Sn(S,Se) and Mo(S,Se)2 will appear in the back interface. These secondary phases will cause serious carrier recombination at the back interface, which will increase the device series resistance (R S ) and reduce the shunt resistance (R Sh ), thus affecting V OCand FF, reducing the overall performance of the device. The introduction of the passivation layer can passivate the defects at the back interface and reduce carrier recombination, thereby improving the open circuit voltage and fill factor of CZTSSe solar cells. At present, ZnO, Ag, C, Bi, Ti, TiN, and Al2O3 are common materials used for battery passivation film layers, and the Al2O3 passivation layer is the most widely used in chalcogenide solar cells. It can be introduced to the back interface by atomic layer deposition (ALD) to achieve the purpose of passivation. However, the above passivation layer materials still have the following disadvantages: (1) They need to be prepared by methods such as magnetron sputtering and atomic layer deposition (ALD), and the related equipment is expensive and cumbersome to operate; (2) These materials usually diffuse into the absorption layer during the high-temperature selenization process, which will affect the element distribution in the bulk phase and is uncontrollable, affecting the performance of the final battery device; (3) Photogenerated carriers usually pass through the passivation film in the form of electron tunneling, and electron tunneling is extremely sensitive to the thickness of the dielectric. Even a sub-nanometer increase in thickness will lead to a significant decrease in the fill factor, making it difficult to optimize the open circuit voltage and fill factor at the same time; (4) For ultra-thin passivation layers, it is very challenging to evenly cover a large rough surface area, which limits their large-area use. Summary of the invention
[0004] The purpose of the present invention is to overcome the above defects and shortcomings in the prior art and provide a method for passivating the back interface of a copper-zinc-tin-sulfur-selenium solar cell based on silicon dioxide nanoparticles.
[0005] The above-mentioned object of the present invention is achieved through the following technical solutions:
[0006] The invention first provides a method for passivating the back interface of a copper-zinc-tin-sulfur-selenium thin-film solar cell, comprising coating a silicon dioxide nanoparticle solution with a mass fraction of 0.14% to 1.5% on a back electrode substrate, cooling after heat treatment, and obtaining a back electrode substrate with silicon dioxide nanoparticles dispersed on the surface.
[0007] The present invention uniformly coats a silica nanoparticle solution on a back electrode substrate, and heat-treats the solvent to evaporate while allowing the silica nanoparticles to adhere to the back electrode substrate, thereby obtaining a back electrode substrate with silica nanoparticles dispersed on the surface, thereby passivating the back interface of a copper-zinc-tin-sulfur-selenium solar cell. Different from a thin film passivation layer, the use of silica nanoparticles to passivate the back interface of the cell allows photogenerated carriers to be directly transmitted to the back interface without the need for traditional electron tunneling. The passivation effect is achieved by directly using silica nanoparticles as an isolation insulating layer to reduce the contact area between the CZTSSe solar cell and the back interface, thereby reducing carrier recombination at the back interface. At the same time, silica nanoparticles are more stable and will not diffuse to the absorption layer during the high-temperature selenization process of preparing a copper-zinc-tin-sulfur-selenium thin film. The present invention adjusts the mass fraction of the silica nanoparticle solution to control the dispersion of the silica nanoparticles on the back interface of the cell, thereby simultaneously increasing the open circuit voltage (V OC ) and fill factor (FF), thereby obtaining a high-efficiency CZTSSe thin-film solar cell. In addition, the process of coating the back electrode substrate with silica nanoparticles is simple and can be directly processed over a large area in the air, which is conducive to large-scale production.
[0008] Furthermore, the silicon dioxide nanoparticle solution is a silicon dioxide nanoparticle aqueous solution.
[0009] Furthermore, the silicon dioxide nanoparticle solution is prepared by ultrasonic dispersion.
[0010] Preferably, the ultrasonic condition is 50-80W ultrasonication for 5-10 min at room temperature.
[0011] Preferably, the ultrasonic condition is 50W ultrasound for 5 min at room temperature.
[0012] Furthermore, the average particle size of the silicon dioxide nanoparticles is 4-200 nm. The silicon dioxide nanoparticles within the particle size range can be used to passivate the back interface of copper-zinc-tin-sulfur-selenium solar cells, so that the prepared solar cells have better device performance.
[0013] Preferably, the average particle size of the silicon dioxide nanoparticles is 4 to 100 nm.
[0014] Furthermore, the coating is spin coating.
[0015] Furthermore, the back electrode substrate is molybdenum-coated glass.
[0016] Furthermore, the back electrode substrate is washed with acetone, ethanol and deionized water in sequence before use.
[0017] Furthermore, the heat treatment is a heat treatment at 100-200° C. for 2-5 min.
[0018] Preferably, the heat treatment is a heat treatment at 100° C. for 2 min.
[0019] The present invention provides application of any of the above methods in improving the performance of copper-zinc-tin-sulfur-selenium thin-film solar cells.
[0020] The present invention provides a method for preparing a copper-zinc-tin-sulfur-selenium thin film, comprising the following steps:
[0021] S1. coating a copper-zinc-tin-sulfur precursor solution on a back electrode substrate having surface-dispersed silicon dioxide nanoparticles obtained by any of the above methods to obtain a copper-zinc-tin-sulfur precursor film;
[0022] S2. Selenize the copper-zinc-tin-sulfur precursor film to obtain a copper-zinc-tin-sulfur-selenium film.
[0023] Furthermore, the copper-zinc-tin-sulfur precursor solution in step S1 is obtained by dissolving copper salt, zinc salt, tin salt and thiourea in a solvent.
[0024] Preferably, the molar ratio of the metal content in the copper salt, zinc salt and tin salt is Cu / Cu+Zn+Sn=0.66-0.75, Zn / Sn=1.07-1.5.
[0025] Preferably, the molar ratio of the metal content in the copper salt, zinc salt and tin salt is Cu / Cu+Zn+Sn=0.66, Zn / Sn=1.5.
[0026] Preferably, the solvent is dimethyl sulfoxide and N,N-dimethylformamide.
[0027] Furthermore, the coating in step S3 is spin coating.
[0028] The invention provides a copper-zinc-tin-sulfur-selenium thin film prepared by the above-mentioned preparation method.
[0029] The invention also provides application of the copper-zinc-tin-sulfur-selenium thin film in preparing a copper-zinc-tin-sulfur-selenium thin film solar cell.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention provides a method for passivating the back interface of a copper-zinc-tin-sulfur-selenium solar cell based on silicon dioxide nanoparticles. The method uniformly disperses a silicon dioxide nanoparticle solution on a back electrode substrate, and uses silicon dioxide nanoparticles as an isolation insulating layer to reduce the contact area between the CZTSSe solar cell and the back interface, thereby reducing carrier recombination at the back interface to achieve a passivation effect; at the same time, during the subsequent selenization process of preparing a copper-zinc-tin-sulfur-selenium thin film, it will not diffuse to the absorption layer, thereby affecting the performance of the battery device. The method of the present invention can improve the open circuit voltage (V OC ), fill factor (FF) and photoelectric conversion efficiency. At the same time, this method has a simple process and can be directly processed on a large area in the air, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the device opening voltage (V OC )Box plot.
[0033] Figure 2 This is a box plot of the fill factor (FF) of devices with different dilution factors obtained in Example 3.
[0034] Figure 3 This is a box plot of device conversion efficiency (PCE) at different dilution factors obtained in Example 3.
[0035] Figure 4 is the device opening voltage (V OC )Box plot. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0037] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0038] Example 1 Preparation of molybdenum glass substrate coated with silicon dioxide nanoparticles
[0039] Step 1: Clean the molybdenum glass substrate by using multi-solvent ultrasonic cleaning of the substrate, and soak it in acetone, anhydrous ethanol, and deionized water in sequence for 15 minutes.
[0040] Step 2: Using 15% water-dispersed silica nanoparticles as the stock solution, prepare water-dispersed silica nanoparticle solutions with different dilution multiples (1:100, 1:50, 1:25, 1:10, 1:5) by 50W ultrasound at room temperature for 5 minutes, that is, water-dispersed silica nanoparticle solutions with mass fractions of 0.1485%, 0.297%, 0.594%, 1.485%, and 2.97%, respectively, wherein the average particle size of the silica nanoparticles (purchased from thermo scientific) is 4 nm; first, it is coated on a cleaned molybdenum glass substrate by spin coating, then placed on a hot stage for heat treatment at 100°C for 2 minutes, and finally cooled naturally.
[0041] Example 2 Preparation of molybdenum glass substrate coated with silicon dioxide nanoparticles
[0042] Step 1: Clean the molybdenum glass substrate by using multi-solvent ultrasonic cleaning of the substrate, and soak it in acetone, anhydrous ethanol, and deionized water in sequence for 15 minutes.
[0043] Step 2: According to the preparation method of Example 1, a water-dispersed solution of silica nanoparticles with a mass fraction of 0.297% was prepared, wherein the average particle sizes of the silica nanoparticles (purchased from thermo scientific) were 4, 20, and 100 nm, respectively. The solution was coated on a cleaned molybdenum glass substrate by spin coating, and then placed on a hot stage for heat treatment at 100°C for 2 min, and finally cooled naturally.
[0044] Example 3 Preparation of CZTSSe Solar Cells
[0045] A precursor ink solution prepared by compound reagents such as copper, zinc, and tin is used to prepare a copper zinc tin sulfur selenide (CZTSSe) film and a solar cell thereof by spin coating.
[0046] Step 1: Preparation of precursor solution: Use an electronic scale to weigh appropriate masses of copper nitrate trihydrate, sodium citrate trihydrate, stannous chloride dihydrate, anhydrous zinc acetate and thiourea (molar ratio Cu / Cu+Zn+Sn=0.66, Zn / Sn=1.5) in sequence, with DMSO and DMF as solvents, to finally obtain a clear, transparent, slightly yellow precursor solution, which is filtered through PTFE before use.
[0047] Step 2: Preparation of copper zinc tin sulfur (CZTS) thin film. The precursor solution prepared in step 1 is coated on the molybdenum glass substrate coated with silica nanoparticles in Example 1 by spin coating. After each spin coating, it is placed on a hot stage and heat treated at 320°C for 2 minutes. The spin coating and heat treatment process is repeated four times to obtain a CZTS precursor film of a certain thickness.
[0048] Step 3: Preparation of copper zinc tin sulfur selenium (CZTSSe) film, in which the CZTS film obtained in step 2 is placed in a graphite box, and Se particles are evenly distributed around the CZTS film, and then placed in a rapid thermal processing furnace for selenization annealing to form a CZTSSe film. The specific selenization conditions in the annealing furnace are: first increase the temperature from room temperature to 400°C within 60 seconds and keep it for 5 minutes, then increase it to 540°C within 90 seconds, and continue to maintain it in a nitrogen atmosphere at normal pressure for 840 seconds, and finally naturally cool it to room temperature and take out the selenized sample.
[0049] Step 4: Device preparation: a 50nm thick cadmium sulfide (CdS) buffer layer is deposited on the CZTSSe film obtained after selenization by chemical bath deposition (CBD); then a 50nm i-ZnO and a 150nm ITO window layer are sputtered by magnetron sputtering; and then a 300nm Ag electrode is evaporated by thermal evaporation to complete the preparation of the entire CZTSSe solar cell.
[0050] Result analysis: Figures 1 to 3 As shown in the figure, compared with the control group, the CZTSSe thin film solar cell prepared by passivating the back interface with silicon dioxide nanoparticles has a lower opening voltage (V OC )( Figure 1 ) and fill factor (FF) ( Figure 2 ) are improved, and high conversion efficiency ( Figure 3 ); among them, the highest opening voltage, filling factor and conversion efficiency of CZTSSe thin film solar cells were obtained by passivating the back interface with a silica nanoparticle aqueous dispersion solution with a mass fraction of 0.297%; the CZTSSe thin film solar cells prepared by passivating the back interface with a silica nanoparticle aqueous dispersion solution with a mass fraction of 0.1485%, 0.594%, and 1.485% also had good opening voltage, filling factor and conversion efficiency, while the CZTSSe thin film solar cells prepared by passivating the back interface with a silica nanoparticle aqueous dispersion solution with a mass fraction of 2.97% had poor performance, with a filling factor (FF) of only 19.58% and a conversion efficiency of 1.16%, which was not included in the statistics due to its low efficiency Figure 2 , 3 The above results show that this method of passivating the back interface of CuZnSnS solar cells based on SiO2 nanoparticles can simultaneously improve the V OC and FF, are beneficial to obtaining high-performance photovoltaic devices.
[0051] Example 4 Preparation of CZTSSe Solar Cells
[0052] A precursor ink solution prepared by compound reagents such as copper, zinc, and tin is used to prepare a copper zinc tin sulfur selenide (CZTSSe) film and a solar cell thereof by spin coating.
[0053] Step 1: Preparation of precursor solution: Use an electronic scale to weigh appropriate masses of copper nitrate trihydrate, sodium citrate trihydrate, stannous chloride dihydrate, anhydrous zinc acetate and thiourea in sequence, with DMSO and DMF as solvents, to finally obtain a clear, transparent, slightly yellow precursor solution, which is filtered through PTFE before use.
[0054] Step 2: Preparation of copper zinc tin sulfur (CZTS) thin film. The precursor solution prepared in step 1 is coated on the molybdenum glass substrate coated with silica nanoparticles in Example 2 by spin coating. After each spin coating, it is placed on a hot stage and heat treated at 320°C for 2 minutes. The spin coating and heat treatment process are repeated four times to obtain a CZTS precursor film of a certain thickness.
[0055] Step 3: Preparation of copper zinc tin sulfur selenium (CZTSSe) film, in which the CZTS film obtained in step 2 is placed in a graphite box, and Se particles are evenly distributed around the CZTS film, and then placed in a rapid thermal processing furnace for selenization annealing to form a CZTSSe film. The specific selenization conditions in the annealing furnace are: first increase the temperature from room temperature to 400°C within 60 seconds and keep it for 5 minutes, then increase it to 540°C within 90 seconds, and continue to maintain it in a nitrogen atmosphere at normal pressure for 840 seconds, and finally naturally cool it to room temperature and take out the selenized sample.
[0056] Step 4: Device preparation: a 50nm thick cadmium sulfide (CdS) buffer layer is deposited on the CZTSSe film obtained after selenization by chemical bath deposition (CBD); then a 50nm i-ZnO and a 150nm ITO window layer are sputtered by magnetron sputtering; and then a 300nm Ag electrode is evaporated by thermal evaporation to complete the preparation of the entire CZTSSe solar cell.
[0057] The experimental results are as follows Figure 4 As shown in Figure 2, the screening of the size of silica nanoparticles further improves the opening voltage (V OC ), but the opening voltage (V OC ) performance is relatively close. It can be seen that when the back interface is passivated by a silica nanoparticle aqueous dispersion solution with a mass fraction of 0.297%, the back interface passivated by different silica nanoparticle sizes has little effect on the performance of the prepared CZTSSe solar cell, while the back interface passivated by a silica nanoparticle aqueous dispersion solution with different mass fractions has a greater effect on the performance of the CZTSSe solar cell.
Claims
1. A method for passivating the back interface of a copper-zinc-tin-sulfur-selenium thin film solar cell, characterized in that: The method comprises coating a silicon dioxide nanoparticle solution with a mass fraction of 0.14% to 1.5% on a back electrode substrate, and cooling after heat treatment to obtain a back electrode substrate with silicon dioxide nanoparticles dispersed on the surface.
2. The method according to claim 1, characterized in that: The silicon dioxide nanoparticle solution is prepared by ultrasonic dispersion.
3. The method according to claim 1, characterized in that: The average particle size of the silicon dioxide nanoparticles is 4 to 100 nm.
4. The method according to claim 1, characterized in that: The back electrode substrate is molybdenum-coated glass.
5. The method according to claim 4, characterized in that: The back electrode substrate is washed with acetone, ethanol and deionized water in sequence before use.
6. The method according to claim 1, characterized in that: The heat treatment is performed at 100-200° C. for 2-5 minutes.
7. Use of the method according to any one of claims 1 to 6 in improving the performance of copper-zinc-tin-sulfur-selenium thin film solar cells.
8. A method for preparing a copper-zinc-tin-sulfur-selenium thin film, characterized in that: The following steps are involved: S1. coating a copper-zinc-tin-sulfur precursor solution on a back electrode substrate having surface-dispersed silicon dioxide nanoparticles obtained by the method of any one of claims 1 to 6 to obtain a copper-zinc-tin-sulfur precursor film; S2. Selenize the copper-zinc-tin-sulfur precursor film to obtain a copper-zinc-tin-sulfur-selenium film.
9. The copper-zinc-tin-sulfur-selenium thin film prepared by the preparation method according to claim 8.
10. Use of the copper-zinc-tin-sulfur-selenium thin film according to claim 9 in preparing copper-zinc-tin-sulfur-selenium thin film solar cells.
Citation Information
Patent Citations
Surface passivation technology capable of improving performance of copper indium gallium selenium thin-film solar cells
CN104143587A
CIGS-based thin-film solar cell and preparation method thereof
CN104867998A
Solar energy cell structure and manufacturing method thereof
CN107068779A
Selenizing method for copper-zinc-tin-sulfur thin film
CN107093639A
Solar cell and preparation method thereof
CN109817749A